Devising investment strategies as a source of financial support to the development of territorial communities in the era of digitalization - Radynskyy, Serghiy; Ratynskiy, Vadym; Lobodina, Zoryana; Shpylyk, Svitlana; Pohrishchuk, Halyna; Dobizha, Nataliia; Bei, Snizhana; Diachenko, Nataliia; Diachenko, Valentyn; Piniak, Iryna (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the process of financial support to the development of territorial communities under the conditions of digitalization. The task addressed was insufficient financial support to territorial communities, which, in turn, limits their development under the conditions of digitalization. The need to devise and implement an investment strategy as a basis of financial support to the development of territorial communities has been identified. The interpretation of the research results demonstrates the significant impact of digitalization on the directions and technologies of the investment strategy of territorial communities. This makes it possible to choose the most popular sources of funding for investment strategies of territorial communities under conditions of digitization. An example of sources of funding for the strategic goals of the digital development of the urban territorial community was given, among which the local budget funds and grant funds prevail. The results prove that the successful development of territorial communities in the era of digitalization depends on their ability to determine target orientations and diversify their funding sources. A distinctive feature of the research results is the construction of a model for the development of territorial communities under conditions of digitalization based on an investment strategy. In order to increase the effectiveness of the process of development and implementation of the investment strategy of territorial communities, the implementation of two-level filtering has been envisaged – according to goals and financial resources. The use of the proposed model would create prerequisites for the further development of territorial communities under the conditions of digitalization. The domain of practical use of the results extends to the management of regional investment development, which involves increasing the size of financial investments and improving the well-being of residents of territorial communities